Writing style modelling based on grapheme distributions : application to on-line writer identification. - Tan, Guoxian. (2013)
The increasingly pervasive spread of mobile digital devices such as mobile smartphones or digital tablets that use digital pens brought about the emergence of a new class of documents; online handwritten documents. The rapid increase in the number of online handwritten documents using such mobile devices leads to mounting pressure on finding innovative solutions towards faster processing, indexing and retrieval of these documents from databases. One such method to address this issue could be to extract writer information derived from the raw ink signal for indexing and retrieval of the documents. Hence, online writer identification is a topic of much renewed interest today because of its importance in applications such as writer adaptation, routing of documents and forensic document analysis.